New Radiocarbon Ages on Percussion-Fractured and Flaked Proboscidean Limb Bones from Yukon, Canada - Holen, Steven R.; Harington, C. Richard; Holen, Kathleen A. (ARCTIC, 2017)
Proboscidean limb bones discovered in Yukon during the 1960s and 1970s exhibit fracture patterns, notches, and bone flakes that are characteristic of percussion. Because of the unique properties of thick cortical proboscidean bone (probably woolly mammoth Mammuthus primigenius or less likely American mastodon Mammut americanum), some researchers hypothesized that these fracture patterns represent intentional hammerstone modification by humans for marrow extraction and bone tool production. As such, these fracture patterns represent evidence of early human dispersal into Eastern Beringia. Radiocarbon dating in the late 1980s indicated that the bone breakage occurred between about 25 000 and 40 000 radiocarbon years before present (14C yr BP). We report 11 new radiocarbon ages using ultra-filtration methods on a different sample of similarly fractured and flaked bones from Yukon. Only two of the radiocarbon ages fall within the expected range of 25 000 to 40 000 14C yr BP. Six other ages are non-finite, with five being more than 49 100 14C yr BP. Three finite ages range between 46 500 and 50 500 14C yr BP with large standard deviations, and these ages may also be non-finite. Two testable hypotheses to explain the observed breakage patterns were developed, the first being that humans broke the bones and the second that some presently unknown geological process broke the bones. Further research is needed to test these two hypotheses. Des ossements de membres de proboscidiens découverts au Yukon dans les années 1960 et 1970 présentent des structures de fractures, des encoches et des traces d’enlèvements d’éclats caractéristiques de la percussion. En raison des propriétés uniques de l’os cortical proboscidien (provenant probablement d’un mammouth laineux Mammuthus primigenius ou, ce qui est moins probable, d’un mastodonte américain Mammut americanum), certains chercheurs ont avancé une hypothèse selon laquelle ces structures représentent des modifications intentionnelles faites au marteau en pierre par des humains, ...